Strontium Accumulations by Teucrium polium which Grows Naturally in Serpentine Soils - Konakcı, Nevin (My University, 2024)
The study area is located in the Guleman region which hosts Turkey's most important chromite deposits and extensive serpentine soils. In this study, strontium uptake accumulations in the shoots and roots of the Teucrium polium plant growing on serpentine soils in the Guleman region were examined. In this context, 17 Teucrium polium plants growing in different locations of serpentine soils were collected together with their shoots, roots and soil, and then chemically analyzed for strontium. Chemical analyses were carried out in ICP-MS. On average, strontium values of 15.2 ppm in the soil, 26.4 in the root and 76.3 ppm in the shoots were detected. Strontium enrichment values in the soil, roots and shoots of this plant were determined as 1.8 for ECR (The enrichment coefficient for root), 5.3 for ECS (The enrichment coefficient for shoot) and 2.9 for TLF (Translocation factor). Results of this study show that the Teucrium polium plant accumulates significant amounts of strontium from the soil, both in the root and in the shoots. As a result, this plant can be used as a bioaccumulator plant, especially in the reclamation of strontium-polluted soils and the improvement of such areas.
Keywords: Strontium; Teucrium Polium; Guleman; Serpentine Soils Accumulation